Competencies of nursing students on primary health care as perceived by faculty and nursing students in Khon Kaen University, Thailand - Porntipa Sombut
This study aimed to determine the competencies of graduating nursing students Class 1988 in integrating primary health care concepts in the care of clients during their clinical learning experiences as perceived by their instructors and students themselves at Faculty of Nursing, Khon Kaen University, Thailand. Specifically, it sought to:1. Determine the adequacy of clinical experiences of nursing students in the development of primary health care competencies as perceived by faculty and students.2. Determine the extent by which primary care competencies have been in the nursing students as perceived by faculty and students.3. Determine the difference between the faculty members' and students' perceptions on the adequacy of clinical experiences and competency of students.4. To find out if there is a correlation between the adequacy of clinical experiences and the competency of students on primary health care as perceived by faculty and students.The students' perceptions of their clinical experiences were gauged with the use of designed questionnaire adapted from Likert Scale.The subjects were all of the graduating nursing students and all of the nursing faculty. 20 nursing students and 5 nursing faculty members were used in pre-testing the instruments. The following were the findings of the study:1. The graduating students had moderate to very adequate experience in integrating primary health care in the care of clients in all areas of nursing. For activities involving clients in analysis of the data obtained, identifying health problems, and in the encouraging clients to use herbal medicines, they had slight adequate experience in the areas of medical-surgical, obstetric, and pediatric nursing.2. The graduating students had moderate to maximal competency in integrating primary health care in all activities in all 5 areas of nursing except in the activity of encouraging medical-surgical clients use of herbal medicine in which they still lack the knowledge and confidence.3. There was significant difference between the faculty members' and students' perceptions of students' competency in involving clients in the analysis of data obtained and in encouraging clients to administer herbal medicine. The students had higher rating than faculty in area of medical surgical, obstetric and pediatric nursing.4. There was a high degree of correlation between the adequacy of clinical experiences and competency in integrating primary health care in area of psychiatric nursing for assessing community health and reinforcing the family to carry out rehabilitation measures; in areas of pediatric and obstetric nursing for encouraging clients to use herbal medicine.